(3JWhQ GdCMcGe GdabgjI aj GdbVGjG GdeGdjI (B/s - (3GdLYHQj, eMeO WGQbs ((3YeGf, GdCQOf (B:s (3OGQ GdfaGFS ddfTQ hGdJhRjY,s, 2012)
(3dG JNai CgejI JWhQ GdCMcGe GdabgjI aj GdeLGd GdeGdj MjK GfJTQJ aj gPG GdYUQ GdYOjO ef GdbVGjG GdeGdjI GdeYGUQI GdJj JMJGL Edi OQGSI JCUjdjI hJTQjYjI(B.s
(3HHdjhLQGajI (B: (3U(B. 419-443.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdeYGedGJ (B((3abg ESdGej(B)s